Synthesis of sulfur‐doped porous carbon for supercapacitor and gas adsorption applications. (29th September 2021) - Mishra, Ranjit; Panda, Prajnashree; Barman, Sudip
Summary: Heteroatom‐doped porous carbon materials have great potential for both capacitive energy storage and gas sorption applications. This article reports the synthesis of highly porous sulfur‐doped carbon from thiophene using an in situ self‐doping strategy followed by KOH activation. A series of highly porous sulfur‐containing carbon materials with high surface area and pore volume were prepared through variation of activation temperature from 600°C to 900°C and applied as supercapacitor electrodes in alkaline as well as neutral electrolyte and also as adsorbent for CO2, H2 adsorption. The material prepared at 800°C presented the highest electrochemical performance with a specific capacitance of 300 F g −1 at 1 A g −1 in 6 M KOH because of its high surface area and pore volume. The presence of oxidized sulfur functionality, high surface area, and micro‐mesoporous structure were the responsible factors for enhanced storage of gases like CO2 and H2 . The functionalized carbon showed a good H2 uptake value of 2.8 wt% under 1 bar pressure at 77 K. CO2 uptake capacities were found to be 5.6 and 3.3 mmol g −1 at 1 bar pressure under the temperature of 273 and 298 K, respectively with a good CO2 /N2 selectivity of 14.36 and CO2 /CH4 selectivity of 2.53. This report presents a promising porous sulfur‐doped carbon material for cost‐effective and efficient gas adsorption and energy storage systems. Abstract : Highly porous S‐doped carbon (SPCs) materials with a surface area of more than 3000 m 2  g −1 were prepared from thiophene followed by KOH activation. The synthesized SPCs show excellent capacitive behavior along with high CO2 and H2 adsorption.